Fenton-like oxidation of reactive black 5 solution using Fe-rice husk ash catalyst - Nor Khonisah, Daud; B. H., Hameed; Nurul Sa'aadah, Sulaiman (2011)
In this work, the decolorization of the azo dye Reactive Black 5 (RB5) was studied, making use of a Fenton-like oxidation process. For that, hydrogen peroxide (H2O) activation was achieved by means of one supported material-based catalysts, which have been immobilized with 0.070 wt. % of Fe (III) oxide on rice husk ash (Fe-RHA). The effects of different parameters such as iron loading (Fe3+2) on rice husk ash (RHA), catalyst dosage, solution pH, initial oncentration of H2O on the decolorization efficiency of the process were studied. The results indicated that by using prepared catalyst with optimum condition (3.5 g L2-1 catalyst dosage of 0.070 wt.% Fe-RHA at pH 2.5 and 20 mM of H2O), 99 % of the 50 mg L -12 of RB5 was decolorized within 150 min. Leaching test indicated that the leached iron from the catalyst was less than 5 mg L-1 which is within the Malaysia regulation of Environmental quality Act 1974.